SISTEM PAKAR DIAGNOSA PENYAKIT TUBERKULOSIS (TBC) PADA RUMAH SAKIT UMUM DAERAH (RSUD) BESEMAH PAGARALAM - Cik, Idi Jang ; Jeksen , Maikel (JURNAL ILMIAH MATRIK, 2016)
Along with the development of technology, also developed a technology system capable of adopting processes and human thinking is an expert system that contains a certain knowledge so that everyone can use it to solve a problem that is specific, in this case is to build a knowledge-based system of doctors to diagnose panyakit tuberculosis , Using PHP with MySQL database. Methods of an expert system is forward chaining with the decision-making tables of supporting data quoted from the relevant experts and other supporting materials. With the facilities provided to users and administrators, allowing both users and administrators to use the system according to their respective needs. Users are given the ease in knowing information of tuberculosis with clinical symptoms, as well as appropriate consultation with a doctor through several questions that must be answered user to find out the diagnosis. While the administrators a simple way to manage the system, both processes add, delete or update the latest data. Keywords: expert system, TBC, PHP, MySQL.